MENDORONG PROGRAM KEMISKINAN DAN RASKIN BERBASIS LOKAL - Pande Made Kutanegara; Endang Ediastuti; Sri Purwatiningsih (Populasi, 2007)
In order to recover from the economy crisis, the government has launced a program namely raskin (beras miskin/rice for poor). This program was addressed to only poor people with criteria set by BPS. Since this program has caused public jeolousy, the criteria for the recepients of raskin then has changed so the term bagita/bagi rata/equally shared came up. All people, whether they were poor or not, then entitled to raskin in various amount every month. This paper will describe in detail the share of raskin and the changing in the criteria based on the research in Kulon Progo Regency and Cilacap Regency.